Microsurgical free tissue transfer as a valuable reconstructive procedure in foot reconstruction - El-Shazly Mohamed; Makboul Mohamed (Indian Journal of Plastic Surgery)
Background: Owing to the limited soft tissue donor sites in the foot area, the use of microsurgical tissue transfer is frequently becoming mandatory in this area, especially in cases of massive defects due to the common motor vehicle accidents in the territory of Upper Egypt. Free flaps offer a great variety of available tissues to cover larger, multifocal or multistructural defects. They also improve the perfusion of the infected poorly perfused areas. Objectives: In this study, we tried to evaluate foot defects according to their size, shape and site and to determine the general and specific parameters of free tissue transfer to the foot area in concomitance with the patients needs. Materials and Methods: Eleven patients were included in this study. For each patient, complete history was taken, general and local examination, photographic documentation, laboratory investigations, imaging and other investigations were performed. Free flap transfers were applied in all cases as follows: Latissimus dorsi flap in five cases, Rectus abdominis flap in three cases, Scapular flap in one case, Gracilis flap in one case and Radial forearm flap in one case. Results: Nine flaps survived. No infection or donor site complications were recorded. Every patient had the optimum free flap as regards the defect size, site, depth, condition, shape, donor site availability and the recipient vessels′ condition. Conclusion: The study of the optimum free flap for foot reconstruction in relation to the defect present and patient conditions is crucial to have significant results.